The Paradox of Cyber Warfare and Clausewitz’s Conception of War - Nageen Ashraf (NUST Journal of International Peace and Stability)
The technological advancements of the 21st century have broadened the traditional concepts of warfare and security. This broadened notion of warfare and security contains an important element of cyberspace. Cyberspace is the virtual space created through the linkages of the internet and internet devices. Because of certain developments, cyberspace is now considered the fifth operational domain for warfare, with the other four domains being land, sea, air, and space. This new realm of confrontation has encouraged states worldwide to secure their cyberspaces and build offensive or defensive cyber warfare capabilities as per their potential. Where traditional realists argue that cyber warfare does not fit the concept of warfare (as proposed by Clausewitz), this article justifies otherwise. The study employs content analysis as a method and adopts a qualitative approach to data analysis, posing the following research question: How does cyber warfare fit Clausewitz’s conception of war? In exploring this, the research hypothesizes that an in-depth analysis of Clausewitz’s trinity -- the elements of violence, combat, and policy -- indicates that these elements are also the salient features of cyber warfare, making it a valid form of war despite its anomalies.